Percepción en atención primaria de salud y la calidad de vida de los adultos mayores atendidos en el Centro de Salud Belén – Loja - Reyes Pinta, Josselyn Antonieta (2024)
Quality of life is considered as the subjective personal perception of the overall environment in which each individual develops, whereas the quality of primary care stems from the individual perspective of the care received. The present research aimed to identify the type of experience elderly adults have when attending primary health care, evaluate their quality of life according to age groups and gender, and establish the relationship between primary health care and the quality of life of elderly adults attending Centro de Salud Belén – Loja during the period from June to December 2022, with a quantitative approach involving a population of 91 elderly adults, who were administered the Primary Care Assessment Tools Questionnaire (PCAT – adult users). The results showed that 57.63% (n=34) of female respondents reported a high experience, while 56.30% (n=18) of male respondents reported a low experience within the overall rating (≥ 6.6; < 6.6). Additionally, the WHOQOL-OLD questionnaire for Quality of Life in Older Adults was employed, revealing that 83.52% (n=76) of elderly adults of both genders exhibited a good quality of life, with a predominance of females at 35.59% (n=21) compared to 25.00% (n=8) of males. It is concluded that the studied variables demonstrated statistical independence, indicating that the quality of primary care and quality of life depends on the perspective and environment of each individual. Given this precedent, it is essential to strengthen the weaknesses of the primary care attributes that received the lowest scores. Additionally, it is recommended that family members become involved in the health and activities of elderly adults to improve their quality of life